banking supervision tools and its impact in inenhancing the service quality: Exploratory research for a sample of Iraqi governmental private bank employees - Hamed Hassan, Abbas; Ali Khaleel, Ameer (Iraqi Journal for Administrative Sciences, 2024)
The search aimed to measure the effect of banking supervision in enhancing the quality of services provided, as a random sample of bank managers and heads of departments working in Iraqi governmental and private banks was selected and their opinions were collected by distributing a questionnaire electronically using Google models to show the extent to which banking supervision tools could be applied and their impact on enhancing The quality of services provided in Iraq. The effect hypothesis was tested using the SPSS V.23 program and according to the regressive deletion model for a sample of 70 employees as a department or division official in a sample of government and private banks. The study found that there is a significant effect of banking control tools in the dimensions of banking service quality (reliability, response, safety, empathy, tangibility). The research found the need for banks to inform the relevant authorities about any suspicious banking operation or service, as well as to encourage working individuals to deal professionally and provide legal protection for workers when reporting any suspicious banking transaction, and then follow up on customer affairs within the bank, which is reflected positively in the quality of The offered service.